AOCR: adaptive on chip router algorithm for multicore domain controller platform - Shanmuganathan, T; Ramachandraiah, U (International Journal of Engineering and Technology, 2018)
In the recent years, with the rapid development of semiconductor technologies and increasing demand for more effective multi-Core Domain Controller platforms, there is a clear demand for effective routing algorithms that can be used to route the packets between these platforms, while enhancing an on chip network performance, achieving a better latency and throughput. This paper proposes an adaptive on Chip Router algorithm with a simple adaptive routing algorithm based on runtime weighted arbitration and resource allocation methodology, where the routing decisions are minimized for applications-specific MDCU platforms. The proposed scheme is evaluated by simulations and its performance in terms of latency, area, power consumption and cost reduction per vehicle are presented. The results show that, 24.5% of latency reduction, 62.25% area utilization optimization and 63.76% of energy efficient compare with existing methods.Â Â